2020
DOI: 10.1037/spy0000189
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and trait self-control interact with the intention–behavior gap in physical activity behavior.

Abstract: Regular physical activity is an empirically well-documented health behavior. Despite the fact that many individuals intend to exercise, they often fail to implement this intention into behavior. Planning is an effective technique for translating physical activity intentions into actions. The present study aimed to examine relevant mediators and moderators in order to explain how and for whom intentions translate into action. In a longitudinal study, 108 participants (M age ϭ 31.17 years, 61 women) from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Some existing studies addressed the mediating role of perceived stress in relationships between different concepts and psychological behavioral responses in different settings. For example, a study conducted by Pfeffer et al ( 94 ) indicated the moderating role of perceived stress and trait self-control in the context of intention and physical activity behavior. It has also been found that nearly half of the total effect of self-compassion on health behavior occurred through perceived stress ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some existing studies addressed the mediating role of perceived stress in relationships between different concepts and psychological behavioral responses in different settings. For example, a study conducted by Pfeffer et al ( 94 ) indicated the moderating role of perceived stress and trait self-control in the context of intention and physical activity behavior. It has also been found that nearly half of the total effect of self-compassion on health behavior occurred through perceived stress ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…PA Intention was assessed using a standardized scale ( Ajzen, 1991 ; Pfeffer et al, 2020 ) including 3 items: “I intend to be physically active for at least 30min per day with moderate-to-vigorous intensity,” “I plan to be …,” and “I am determined to be ….” These items had to be answered on 6-point Likert scales from 1 (strongly disagree) to 6 (strongly agree). Internal consistency for the intention scale was calculated at α =0.86 in this study, indicating good reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Pfeffer, Englert, and Mueller-Alcazar (2020) investigated hypothesized mediators and moderators of the physical activity intention–behavior gap in an attempt to explain how and for whom intentions translate into action. The results of a moderated-mediation analysis revealed that perceived stress and trait self-control interact with physical activity intentions to predict physical activity behavior, indicating that trait self-control might serve as a buffer against the negative effects of stress.…”
Section: Overview Of Articles In the Current Special Issuementioning
confidence: 99%
“…More specifically, the studies in this issue provide intriguing avenues for future research that may lead to a better understanding of the relationship between state fluctuations in self-control and physical performance as well as dispositional characteristics of individuals that may affect, or be affected by, physical activity. For example, the studies by Stocker et al (2020) and Pfeffer et al (2020) highlight the importance of investigating theory-based psychological mediators of self-control and behavior in future studies, whereas the study by O’Brien and colleagues (2020) demonstrates the use of noninvasive technology that may provide new perspectives on neurophysiological mechanisms underlying self-control. When considering in concert with findings from the other studies in this issue and the broader self-control literature, our understanding of how and when self-control depletion effects occur will benefit from assessing potential mechanisms that may be shared among tasks that require self-control and manipulated by interventions that can be designed to target those underlying mechanisms.…”
Section: Common Themes and Conclusionmentioning
confidence: 99%